Pengaruh Pendekatan SAVI Terhadap Keterampilan Pementasan Drama Siswa Kelas VIII SMP Negeri 35 Palembang - Rahmawati, Dewi; Murniviyanti, Liza; Armariena, Dian Nuzulia (Indonesian Research Journal on Education, 2023)
This study aims to determine the effect of the SAVI approach (Somatic, Auditory, Visual, Intellectual)through research on student learning outcomes of VIII SMP Negeri 35 Palembang. This researchincludes the experimental class and the control class in class VIII.1. The control class consists of 29students and the Experiment class VIII.2 consists of 32 students. This type of research uses the TrueExperiment method which uses two classes of research samples with a Posttest Only Control design. The results of this study indicate that the SAVI approach affects the drama performance skills of class VIII SMP Negeri 35 Palembang. The technique of analyzing student learning outcomes data is using t-test statistical analysis. The results of the study showed that the posttest value of the experimental and control classes obtained the value of t count = 6.29 which was greater than t table = 1.67 (t count > t table). Based on these results, it can be concluded that the hypothesis testing criteria obtain t_(count)= 6.29 while t_(table) =1.67 then H_a is accepted and H_o is rejected. This means that the influence of the SAVI approach (Somatic, Auditory, Visualization, Intellectual) on the drama performance skills of eighth-grade students of SMP Negeri 35 Palembang is significant.